Transforming Science Education: A Systematic Review of Evidence-Based Strategies for Cultivating 21st-Century Skills in STEM Education - Bamidele Emmanuel Tijani; Adeniyi Michael Adeduyigbe (Scientia Publica Media, 2026)
The accelerating demands of the 21st century require science education to evolve beyond traditional content delivery and to cultivate skills such as critical thinking, collaboration, digital literacy, and global awareness. This systematic review examines 20 empirical studies published between 2017 and 2025 to identify evidence-based instructional strategies, namely inquiry-based learning, project-based learning, and integrated STEM approaches and immersive technologies (virtual reality, augmented reality, and simulations) that support the development of these competencies. Studies were retrieved from ScienceDirect (Scopus) and Google Scholar, screened against predefined inclusion and exclusion criteria, and synthesised through thematic analysis. Findings demonstrate that scaffolded inquiry and project-based frameworks consistently enhance critical thinking, creativity, and collaboration, particularly when complemented by structured reflection and visual-tool support. Immersive technologies amplify engagement and conceptual understanding, especially when metacognitive prompts accompany virtual or hands-on laboratory experiences. Integrated-STEM and EthnoVLab models further underscore the value of interdisciplinary, context-rich projects for motivation and higher-order skill acquisition. Equity-centred designs that incorporate assistive technologies and professional development for teachers are shown to be vital for inclusive implementation. Persistent barriers include limited access to technology, insufficient teacher training, and uneven policy support. The review highlights the need for longitudinal, mixed-method, and comparative investigations to assess the durability of 21st-century skill gains and to refine discipline-specific assessment tools. Implications extend to researchers, who should pursue innovative study designs; to policymakers, who must embed interdisciplinary, equity-focused standards and support structures; and to practitioners, who can pilot blended-STEM initiatives with peer-learning networks. Ultimately, this work offers actionable insights for bridging traditional pedagogy and contemporary educational demands, fostering sustainable reforms in science education.